Production method of stainless steel mixed carbon fiber composite spunlaced felt

Through the composite materials of stainless steel fiber and carbon fiber and multi-step process, the problem of imperfect spun felt performance is solved, high strength, corrosion resistance and stability are achieved, and it is suitable for applications in multiple fields.

CN119265951AInactive Publication Date: 2025-01-07JIANGSU FMS ENVIROMENTAL&ENERGY SAVING NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411579431.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing spunlace felt has imperfect performance, uneven fiber mixing, lack of effective bonding and strengthening means, anti-shrinkage, heat resistance, and corrosion resistance, resulting in poor structural stability, limiting its application in chemical and other fields.

Method used

Using composite materials of stainless steel fiber and carbon fiber, high-strength, corrosion-resistant composite water is formed through high-speed stirring, loosening, combing, segmented hydrotubing, pre-drying, waterproof and heat-resistant coating and step-drying drying. Braised felt.

Benefits of technology

Achieve good mechanical properties of composite spunlace in a variety of harsh environments, provide high strength and corrosion resistance, is suitable for areas with high performance requirements, and improves the product through waterproof and heat-resistant coating and uniform adhesion. stability and application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265951A_ABST
    Figure CN119265951A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of spunlace felt production, and discloses a production method of a stainless steel mixed carbon fiber composite spunlace felt, which comprises the following steps: selecting stainless steel fibers and carbon fibers as raw materials; putting the stainless steel fibers and the carbon fibers into a mixing tank, adding a proper amount of a coupling agent, and stirring and mixing at a high speed; conveying to an opener through air flow for opening treatment; carding the opened fibers by using a carding machine; feeding the fiber net into a spunlace machine for spunlace reinforcement; carrying out pre-drying treatment on the spunlaced composite felt; uniformly spraying a waterproof heat-resistant coating on the surface of the pre-dried composite felt; carrying out secondary drying treatment; and cooling to room temperature and then rolling. The stainless steel fibers and the carbon fibers are compounded, the high strength of the carbon fibers and the corrosion resistance of the stainless steel fibers are fully utilized, and a unique production process is combined, so that the spunlaced felt of the composite structure can keep good performance in various severe environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spunlace felt production, and in particular to a method for producing stainless steel mixed carbon fiber composite spunlace felt. Background Art

[0002] Spunlace felt is a nonwoven fabric made by the spunlace process. Its production principle is to use high-pressure fine water flow to spray the fiber web, so that the fibers are entangled with each other to form a cloth-like material. Spunlace felt has various raw materials, including natural fibers and chemical fibers. It has the characteristics of moderate strength, softness and no lint. In the medical and health fields, it can be used to make surgical gowns, medical dressings, etc.; in the home and cleaning fields, it is the base material of wet wipes and is also used for home decoration; in the industrial field, it can be used for primary filtration and automotive interior, etc. It is a material with multi-faceted application value.

[0003] There are many shortcomings in the existing spunlace felt technology. On the one hand, traditional spunlace felt mostly uses a single fiber and has relatively simple performance. On the other hand, there are defects in the production process, uneven fiber mixing, and lack of effective bonding and reinforcement methods. In addition, ordinary spunlace felt is obviously insufficient in environmental resistance such as shrinkage resistance, heat resistance, and corrosion resistance, which can easily lead to poor structural stability and limited application in chemical and other fields. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for producing a stainless steel mixed carbon fiber composite spunlace felt, which solves the problem of imperfect performance of the spunlace felt produced by the prior art.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for producing a stainless steel mixed carbon fiber composite spunlace felt, comprising the following steps:

[0006] S1. Select stainless steel fiber with a diameter of 0.01mm-0.05mm and carbon fiber with a length of 1mm-5mm as raw materials;

[0007] S2. The stainless steel fiber and the carbon fiber are placed in a mixing tank in a mass ratio of 1:2-2:3, an appropriate amount of coupling agent is added, and the mixture is stirred at a high speed of 150 r / min-250 r / min for 45 min-75 min;

[0008] S3. The mixed fibers are transported to an opener through airflow for opening. The beater speed of the opener is 1800r / min-2200r / min to ensure that the fibers are fully loosened;

[0009] S4. The fibers after opening are combed by a carding machine, the cylinder speed of the carding machine is 10m / s-15m / s, and the doffer speed is 4m / s-6m / s to form a uniform fiber web, and the thickness of the fiber web is controlled at 0.5mm-1.5mm;

[0010] S5. The fiber web is fed into the spunlacing machine for spunlacing reinforcement. The spunlacing pressure is set to 60MPa-90MPa, the number of spunlacing heads is 4-7, the spunlacing angle is 25°-35°, and the spunlacing speed is 4m / min-7m / min;

[0011] S6. The composite felt after spunlace is pre-dried at a temperature of 60°C-80°C for a drying time of 30min-50min;

[0012] S7. Evenly spray a layer of waterproof and heat-resistant coating on the surface of the pre-dried composite felt, with a coating thickness of 0.01mm-0.04mm;

[0013] S8. Perform secondary drying treatment at a drying temperature of 100°C-130°C and a drying time of 45min-75min;

[0014] S9. Cooling the composite spunlace felt obtained after the secondary drying, and rolling it up after cooling to room temperature.

[0015] Preferably, the coupling agent is a silane coupling agent, and the added amount thereof is 0.5%-1.5% of the total mass of the fiber.

[0016] Preferably, in S5, a segmented hydroentanglement process is adopted, wherein preliminary hydroentanglement is first performed at a relatively low pressure of 60 MPa-70 MPa, and then the pressure is gradually increased for deep hydroentanglement.

[0017] Preferably, the waterproof and heat-resistant coating is composed of a nano-scale waterproof agent and a heat-resistant resin in a mass ratio of 1:3-1:5, and has good waterproof and heat-resistant properties.

[0018] Preferably, in S8, a step-by-step heating method is adopted to avoid adverse effects of sudden temperature changes on the composite felt.

[0019] Preferably, in S9, a combination of natural cooling and air cooling is adopted, and the cooling rate is controlled at 2°C / min-5°C / min.

[0020] Preferably, the heat-resistant resin is a polyimide resin, and the nano-scale waterproofing agent is a nano-silicon dioxide waterproofing agent.

[0021] The present invention provides a method for producing a stainless steel mixed carbon fiber composite spunlace felt.

[0022] Beneficial effects:

[0023] 1. The present invention makes full use of the high strength of carbon fiber and the corrosion resistance of stainless steel fiber by compounding stainless steel fiber and carbon fiber. This composite structure enables the spunlace felt to maintain good mechanical properties in a variety of harsh environments and is suitable for fields with high requirements for strength and corrosion resistance.

[0024] 2. The present invention sprays a waterproof and heat-resistant coating composed of nano-silicon dioxide waterproofing agent and polyimide resin on the surface of the copper drum composite felt. The nano-silicon dioxide can fill the gaps between fibers to form a hydrophobic layer, effectively preventing water penetration, and the polyimide resin provides excellent heat resistance, ensuring that the product has stable performance in a high temperature environment, and can be used for heat insulation and protection in a high temperature and humid environment.

[0025] 3. The present invention adds silane coupling agent during the fiber mixing process and reasonably controls the stirring speed and time to evenly distribute the coupling agent on the fiber surface, thereby enhancing the bonding force between fibers, reducing the formation of fiber agglomerates, ensuring the consistency of the performance of the composite spunlace felt, and providing high-quality raw materials for subsequent processing.

[0026] 4. The present invention adopts a segmented spunlace process, which first uses a relatively low pressure to initially spunlace the fiber web, and then gradually increases the pressure to perform deep spunlace to tightly entangle the fibers. This process effectively improves the strength and stability of the composite spunlace felt, and is more advantageous than a single pressure spunlace process.

[0027] 5. The secondary drying of the present invention adopts a step-by-step heating method to avoid adverse effects of sudden temperature changes on the composite felt, ensuring the stability of coating performance and fiber structure. The cooling method combining natural cooling and air cooling can effectively control the cooling speed, reduce the impact of thermal stress on the product, and ensure the dimensional stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for producing a stainless steel mixed carbon fiber composite spunlace felt, comprising the following steps:

[0032] S1. Select stainless steel fiber with a diameter of 0.02mm and carbon fiber with a length of 3mm as raw materials. The high strength of carbon fiber and the corrosion resistance of stainless steel fiber complement each other, so that the composite spunlace felt has excellent performance in strength and corrosion resistance;

[0033] S2. Put the stainless steel fiber and the carbon fiber into a mixing tank at a mass ratio of 1:2, add silane coupling agent accounting for 1% of the total mass of the fiber, and stir at a speed of 200r / min for 60min. The silane coupling agent forms a chemical bond on the fiber surface, enhances the bonding force between the fibers, improves the overall strength and stability of the composite spunlace felt, and also improves the adhesion between the fiber and the subsequent coating, ensuring that the waterproof and heat-resistant coating can be firmly attached to the fiber surface to exert its waterproof and heat-resistant functions. Reasonable control of the stirring speed and time makes the coupling agent evenly distributed on the fiber surface to avoid local agglomeration or uneven distribution, thereby ensuring the performance consistency of the composite spunlace felt. Sufficient stirring can also promote the dispersion between the fibers and reduce the formation of fiber agglomerates, providing a good raw material basis for subsequent processing;

[0034] S3. The mixed fibers are transported to the opener by airflow. The beater speed of the opener is 2000r / min. The use of airflow to transport fibers can avoid damage to the fibers during mechanical transportation, maintain the integrity of the fibers, and make the fibers enter the opener more loosely, thereby improving the opening effect.

[0035] S4. The opened fibers are combed by a carding machine. The cylinder speed of the carding machine is 12 m / s and the doffer speed is 5 m / s to form a fiber web with a thickness of 1 mm. Reasonable control of the cylinder speed and doffer speed of the carding machine can control the thickness and uniformity of the fiber web, avoiding the fiber web being too thick or too thin, which affects the performance of the product. A uniform fiber web can ensure the performance consistency of the composite spunlace felt in all directions and improve the overall quality of the product.

[0036] S5. The fiber web is fed into the spunlacing machine, and the initial spunlacing is performed at a pressure of 65 MPa, and then the pressure is gradually increased to 80 MPa for deep spunlacing. The number of spunlacing heads is 5, the spunlacing angle is 30°, and the spunlacing speed is 5 m / min. The segmented spunlacing process can initially fix the fiber web to avoid excessive displacement of the fiber during the subsequent high-pressure spunlacing process, and then the pressure is gradually increased for deep spunlacing, which can make the fibers more tightly entangled and improve the strength and stability of the composite spunlaced felt;

[0037] S6. Pre-dry the composite felt after spunlaced at a temperature of 70°C for 40 minutes and a hot air speed of 2 m / s, so as to remove most of the water in the composite felt and make it reach a suitable water content, thus providing a good foundation for subsequent coating and secondary drying processes;

[0038] S7. Evenly spray a waterproof and heat-resistant coating composed of nano-silica waterproofing agent and polyimide resin in a mass ratio of 1:4 on the surface of the pre-dried composite felt, and the coating thickness is 0.03 mm. The nano-silica waterproofing agent has an extremely small particle size and can be filled into the tiny gaps between the fibers to form a hydrophobic layer to effectively prevent water penetration. The polyimide resin has excellent heat resistance and can maintain stable performance without deformation in a high temperature environment;

[0039] S8. Perform secondary drying treatment by using a step-wise heating method, first raising the temperature from room temperature to 100°C at a heating rate of 6°C / min and maintaining it for 12 minutes; then raising the temperature to 118°C at a heating rate of 4°C / min and maintaining it for 25 minutes; finally, raising the temperature to 130°C at a heating rate of 3°C / min and maintaining it for 15 minutes;

[0040] S9. The composite spunlace felt after secondary drying is cooled by a combination of natural cooling and air cooling. The cooling rate is controlled at 3°C / min. After cooling to room temperature, it is rolled up. The combination of natural cooling and air cooling can allow the spunlace felt to dissipate heat evenly, making the temperature changes of the inner and outer layers more synchronous, effectively reducing the generation of thermal stress, avoiding damage to the spunlace felt structure and coating due to rapid temperature changes, and improving the stability of the spunlace felt performance. Rolling up in a cooled state can prevent the heat inside the spunlace felt from being difficult to dissipate. Under the action of winding pressure, it may cause local overheating and deformation, affecting the product appearance and performance.

[0041] Embodiment 2:

[0042] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for producing a stainless steel mixed carbon fiber composite spunlace felt, comprising the following steps:

[0043] S1. Select stainless steel fiber with a diameter of 0.04 mm and carbon fiber with a length of 4 mm as raw materials;

[0044] S2. The stainless steel fiber and the carbon fiber were placed in a mixing tank in a mass ratio of 1.5:2.5, and a silane coupling agent accounting for 1.2% of the total mass of the fiber was added, and stirred at a speed of 220 r / min for 50 min;

[0045] S3. The mixed fibers are transported to the opener by airflow, and the beater speed of the opener is 2100r / min;

[0046] S4. The fibers after opening were combed using a carding machine, the cylinder speed of the carding machine was 13 m / s, the doffer speed was 5.5 m / s, and a fiber web having a thickness of 1.2 mm was formed;

[0047] S5. The fiber web is fed into the hydroentanglement machine, and the initial hydroentanglement is performed at a pressure of 68 MPa, and then the pressure is gradually increased to 85 MPa for deep hydroentanglement. The number of hydroentanglement heads is 6, the hydroentanglement angle is 32°, and the hydroentanglement speed is 6 m / min;

[0048] S6. The composite felt after spunlace was pre-dried at a drying temperature of 75 ° C, a drying time of 45 min, and a hot air speed of 2.5 m / s;

[0049] S7. After pre-drying, a layer of waterproof and heat-resistant coating composed of nano-silica waterproofing agent and polyimide resin in a mass ratio of 1:3.5 is evenly sprayed on the surface of the composite felt, and the coating thickness is 0.025mm;

[0050] S8. Perform secondary drying treatment by using a step-wise heating method, first raising the temperature from room temperature to 100°C at a heating rate of 7°C / min and maintaining it for 10 minutes; then raising the temperature to 116°C at a heating rate of 4.5°C / min and maintaining it for 28 minutes; finally, raising the temperature to 130°C at a heating rate of 3.5°C / min and maintaining it for 18 minutes;

[0051] S9. The composite spunlace felt after secondary drying is cooled by a combination of natural cooling and air cooling, with the cooling rate controlled at 4°C / min, and is rolled up after being cooled to room temperature.

[0052] Embodiment three:

[0053] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for producing a stainless steel mixed carbon fiber composite spunlace felt, comprising the following steps:

[0054] S1. Select stainless steel fiber with a diameter of 0.03 mm and carbon fiber with a length of 2.5 mm as raw materials;

[0055] S2. Put the stainless steel fiber and the carbon fiber in a mixing tank in a mass ratio of 2:3, add 0.8% of the total mass of the fiber silane coupling agent, and stir at a speed of 180r / min for 70min;

[0056] S3. The mixed fibers are transported to the opener by airflow, and the beater speed of the opener is 1900r / min;

[0057] S4. The fibers after opening are combed by a carding machine, the cylinder speed of the carding machine is 11 m / s, the doffer speed is 4.5 m / s, and a fiber web having a thickness of 0.8 mm is formed;

[0058] S5. The fiber web is fed into the hydroentanglement machine, and the initial hydroentanglement is performed at a pressure of 62 MPa, and then the pressure is gradually increased to 75 MPa for deep hydroentanglement. The number of hydroentanglement heads is 4, the hydroentanglement angle is 28°, and the hydroentanglement speed is 4.5 m / min;

[0059] S6. The composite felt after spunlace was pre-dried at a drying temperature of 65 ° C, a drying time of 48 min, and a hot air speed of 1.8 m / s;

[0060] S7. After pre-drying, a layer of waterproof and heat-resistant coating composed of nano-silica waterproofing agent and polyimide resin in a mass ratio of 1:4.5 is evenly sprayed on the surface of the composite felt, and the coating thickness is 0.035mm;

[0061] S8. Perform secondary drying treatment by using a step-wise heating method, first raising the temperature from room temperature to 100°C at a heating rate of 5.5°C / min and maintaining for 15 minutes; then raising the temperature to 117°C at a heating rate of 3.5°C / min and maintaining for 22 minutes; finally, raising the temperature to 130°C at a heating rate of 2.5°C / min and maintaining for 12 minutes;

[0062] S9. The composite spunlace felt after secondary drying is cooled by a combination of natural cooling and air cooling, with the cooling rate controlled at 2.5°C / min, and is rolled up after being cooled to room temperature.

[0063] Comparative Example 1:

[0064] The present invention provides a method for producing a spunlace felt, comprising the following steps:

[0065] S1. Prepare a single polyester fiber as a raw material, the fiber length is 2mm-4mm;

[0066] S2. Put the polyester fiber into a mixing tank, without adding a coupling agent, and stir at a speed of 150r / min for 30min to initially mix the fibers;

[0067] S3. The mixed fibers are delivered to an opener by mechanical conveying, the beater speed of the opener is 1500r / min, and the opener is processed;

[0068] S4. The fibers after opening are combed by a carding machine, the cylinder speed of the carding machine is 8 m / s, the doffer speed is 3 m / s, and a fiber web having a thickness of 0.8 mm is formed;

[0069] S5. The fiber web is fed into a spunlacing machine and spunlaced at a constant pressure of 70 MPa. The number of spunlacing heads is 4, the spunlacing angle is 25°, and the spunlacing speed is 4 m / min.

[0070] S6. The spunlaced felt was dried once at a temperature of 80°C for 50 min at a hot air speed of 1.5 m / s.

[0071] S7. After drying, the product is rolled up directly without coating.

[0072] Comparative Example 2:

[0073] The present invention provides a method for producing a spunlace felt, comprising the following steps:

[0074] S1. Select polypropylene fiber as raw material, the fiber diameter is 0.03mm-0.06mm;

[0075] S2. Put the polypropylene fiber into a mixing tank without adding any additives and stir at a speed of 180r / min for 40min;

[0076] S3. The fibers are transported to the opener by air flow, and the beater speed of the opener is 1800r / min;

[0077] S4. The fibers after opening are combed by a carding machine, the cylinder speed of the carding machine is 10 m / s, the doffer speed is 4 m / s, and a fiber web having a thickness of 1 mm is formed;

[0078] S5. The fiber web is fed into the hydroentanglement machine, and the initial hydroentanglement is performed at a pressure of 60 MPa, and then the secondary hydroentanglement is performed at a pressure of 75 MPa. The number of hydroentanglement heads is 3, the hydroentanglement angle is 28°, and the hydroentanglement speed is 4.5 m / min;

[0079] S6. The spunlaced felt was pre-dried at a temperature of 65°C, a drying time of 45 min, and a hot air speed of 1.8 m / s;

[0080] S7. Without coating treatment, the pre-dried felt is directly subjected to secondary drying at a drying temperature of 90°C, a drying time of 60min, and a hot air speed of 2m / s;

[0081] S8. After cooling to room temperature, roll up.

[0082] The above examples and comparative examples were tested in terms of tensile strength, stability, corrosion resistance and uniformity. The test results are shown in the following table:

[0083]

[0084] In summary, the spunlace felt produced in the embodiments of the present invention has excellent performance in terms of tensile strength, stability, corrosion resistance and uniformity, and has extremely ideal application prospects.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for producing a stainless steel mixed carbon fiber composite spunlace felt, characterized in that: The following steps are involved: S1. Select stainless steel fiber with a diameter of 0.01mm-0.05mm and carbon fiber with a length of 1mm-5mm as raw materials; S2. The stainless steel fiber and the carbon fiber are placed in a mixing tank in a mass ratio of 1:2-2:3, an appropriate amount of coupling agent is added, and the mixture is stirred at a high speed of 150 r / min-250 r / min for 45 min-75 min; S3. The mixed fibers are transported to an opener through airflow for opening. The beater speed of the opener is 1800r / min-2200r / min to ensure that the fibers are fully loosened. S4. The fibers after opening are combed by a carding machine, the cylinder speed of the carding machine is 10m / s-15m / s, and the doffer speed is 4m / s-6m / s to form a uniform fiber web, and the thickness of the fiber web is controlled at 0.5mm-1.5mm; S5. The fiber web is fed into the spunlacing machine for spunlacing reinforcement. The spunlacing pressure is set to 60MPa-90MPa, the number of spunlacing heads is 4-7, the spunlacing angle is 25°-35°, and the spunlacing speed is 4m / min-7m / min; S6. The composite felt after spunlace is pre-dried at a temperature of 60°C-80°C for a drying time of 30min-50min; S7. Evenly spray a layer of waterproof and heat-resistant coating on the surface of the pre-dried composite felt, with a coating thickness of 0.01mm-0.04mm; S8. Perform secondary drying treatment at a drying temperature of 100°C-130°C and a drying time of 45min-75min; S9. Cooling the composite spunlace felt obtained after the secondary drying, and rolling it up after cooling to room temperature.

2. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: The coupling agent is a silane coupling agent, and the addition amount thereof is 0.5%-1.5% of the total mass of the fiber.

3. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: In S5, a segmented hydroentanglement process is adopted, wherein a relatively low pressure of 60 MPa-70 MPa is first used for preliminary hydroentanglement, and then the pressure is gradually increased for deep hydroentanglement.

4. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: The waterproof and heat-resistant coating is composed of a nano-scale waterproof agent and a heat-resistant resin in a mass ratio of 1:3-1:5, and has good waterproof and heat-resistant properties.

5. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: In S6, the wind speed of the hot air is controlled to be 1.5m / s-3m / s to ensure uniform drying.

6. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: In S8, a step-by-step heating method is adopted to avoid adverse effects of sudden temperature changes on the composite felt.

7. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 1, characterized in that: In the S9, a combination of natural cooling and air cooling is adopted, and the cooling rate is controlled at 2°C / min-5°C / min.

8. The method for producing a stainless steel mixed carbon fiber composite spunlace felt according to claim 4, characterized in that: The heat-resistant resin is a polyimide resin, and the nano-scale waterproofing agent is a nano-silicon dioxide waterproofing agent.

Citation Information

Patent Citations

  • Non-base cloth static coupling-removing high-temperature filter material for electric-bag compound dust remover and manufacturing method

    CN101862566A

  • Carbon fiber and basalt composite filtering material

    CN102836592A

  • Carbon fiber electrostatic actuation type dust-removing filter bag and preparation method thereof

    CN104028046A

  • Processing method of carbon fiber filter material

    CN107475890A

  • Preparation method of high-strength and low-resistivity composite conductive plastic

    CN111300914A